Understanding Industry 4. 0 : AI, the Internet of Things, and the Future of Work. - Sergi, Bruno S. (Emerald Publishing Limited, 2019)
With the rapid changes in technology that characterize the Fourth Industrial Revolution comes social evolution and the potential for future social crises. Understanding Industry 4.0 looks to determine the most probable oncoming changes and highlight the most important professions of the future.